A biodegradable friction nano-electricity generating fabric and preparation method thereof
By silver plating and modification of cellulose filaments, the friction nano-powered power generation fabric with a leather core structure is solved, and the environmental pollution problems caused by the use of non-degradable materials in the prior art are improved, and the electrical output performance and water washing resistance of cellulose-based TTENG are improved, achieving the goal of green environmental protection and efficient self-power supply.
Patent Information
- Application Number
- CN202311086733.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-08-28
AI Technical Summary
The existing tribonanoelectric fabrics use non-degradable or non-renewable conductive materials, resulting in environmental pollution and resource consumption, and the electrical output performance, working stability and water washing resistance of cellulose-based TTENG are insufficient.
By electroless silver plating on the cellulose filaments, the conductive silver-plated cellulose filaments are constructed as the conductive inner core, and the cellulose filaments are modified with positive and negative electrodes to form a friction nano-powered fabric with a leather core structure. The fabric is equipped with a high-speed braiding mechanism to adjust the gear ratio to improve the density and electrical output performance of the outer friction layer.
It realizes the high electrical output performance, stability and water washing resistance of cellulose-based friction nano-powered fabrics, and has good biodegradation performance and can be completely degraded within 72 hours.
Smart Images

Figure CN117005060B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intelligent textiles, and in particular relates to a biodegradable friction nano-electricity generating fabric and a preparation method thereof. Background Art
[0002] As an important branch of smart materials, wearable smart sensing materials have great application potential in the fields of human body sensing, artificial intelligence, medical bionics, etc., and will provide unlimited possibilities for human motion monitoring, health testing, etc., and have received extensive attention from domestic and foreign academic circles. Smart wearable fabrics have the characteristics of light weight, low modulus, high softness and elasticity, multi-dimensional structure, low cost, and high skin affinity. Compared with smart bracelets, smart glasses, smart skin and other sensing devices, they have unique advantages in the field of smart wearables. The development of self-powered sensing fabrics that do not require external power is one of the important development directions of smart wearable fabrics today. It not only saves energy, but also greatly improves the portability, comfort and long-term use of the equipment in practical applications, which has important research significance.
[0003] Using the friction electrification (contact electrification) effect, Professor Wang Zhonglin proposed the concept of friction nanogenerator (TENG). TENG can generate electrical signals under external pressure, thereby converting mechanical energy into electrical energy. Combining TENG with traditional textiles, researchers have developed friction nanogenerator fabric (TTENG). TTENG combines the piezoelectric effect of TENG with the soft, breathable and comfortable properties of textiles. It has outstanding application prospects in the field of smart textiles and smart wearables, and has attracted widespread attention from researchers at home and abroad.
[0004] In order to improve the electrical performance, the raw materials used in the preparation of TTENG are usually non-degradable or non-renewable conductive materials (metal wires, carbon-based fibers, or conductive polymers) and polymers (polytetrafluoroethylene, silicone rubber, etc.). Chinese invention patent CN109123854B provides a friction nano-power generation fabric, including a first conductive yarn electrode, a second conductive yarn electrode, a first conductive fabric, a second conductive fabric, and a non-conductive yarn fabric. When the external insulating material and the two conductive fabrics move relative to each other, friction charges can be generated, thereby generating current; in the invention, the raw materials of the first conductive yarn electrode and the second conductive yarn electrode independently include at least one of carbon nanotube yarn, graphene yarn, silver-plated polymer yarn, and metal wire yarn; the first conductive fabric and the second conductive fabric independently use raw materials including at least one of carbon nanotube yarn, graphene yarn, metal-plated polymer yarn, and metal wire yarn. These conductive materials are non-degradable or non-renewable conductive materials, which are easy to pollute the environment.
[0005] In order to reduce the consumption of non-renewable resources such as coal and oil, and effectively avoid the environmental damage caused by waste smart sensor fabrics, the development of degradable or recyclable green and environmentally friendly friction nano-power generation fabrics using natural polymers such as cellulose, chitin, silk fibroin, rice paper, egg white, etc. as raw materials has become an important development direction of self-powered smart fabrics and has important research significance. Chinese invention patent CN109913965B discloses a cellulose / graphene fiber material in situ self-assembled in a co-alkali system and a preparation method thereof, which is composed of a graphene dispersion and a cellulose solution, and the solvent of the cellulose solution is composed of a strong alkali composition, urea or thiourea, and water; the preparation method of the material includes the steps of: intercalation, activation, shear stripping, co-alkali solution dispersion, and obtaining a high-concentration graphene dispersion; cellulose is dissolved in a co-alkali solvent at -12°C to -4°C, and high-speed stirring is performed to quickly obtain a transparent cellulose concentrated solution with high solubility. After mixing the cellulose solution in an alkaline system with the graphene dispersion in a suitable ratio, the cellulose / graphene fiber material is prepared by self-assembly in a 3-5wt% dilute acid coagulation bath, drawing, oiling, and drying. The prepared material can be used for wearable self-generating smart fabrics, antistatic textile materials, flexible smart sensing materials or electromagnetic shielding fabrics, etc., and has good strength and toughness.
[0006] At present, there are few studies on the preparation of all-cellulose TTENG using only cellulose (CNF) as raw material. How to improve the electrical output performance, working stability, water resistance, and wearing comfort of the obtained cellulose-based TTENG through surface chemical modification is the main problem faced in the preparation of cellulose-based TTENG. Therefore, it is of great significance to construct a cellulose-based TTENG and optimize its performance to improve its application value while being environmentally friendly. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a biodegradable friction nano-electric power generation fabric and a preparation method thereof. The preparation method of the present invention comprises the following steps: chemically silver-plating cellulose filaments (CNF-F) to construct electro-silver-plated CNF-F, and preparing conductive silver-plated CNF-F (AgNPs CNFs) as a conductive inner core; then the cellulose filaments are modified, and the positive cellulose filaments and the negative cellulose filaments after positive and negative grafting modification of CNF-F are woven on the outside of AgNPs CNFs to tightly wrap the conductive inner core, and composite yarns are respectively constructed. The formed skin-core structure is used for the preparation of cellulose-based friction nano-electric power generation fabric, which not only has good biodegradability, but also meets the needs of intelligent self-powered sensing.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] First, the present invention provides a biodegradable friction nano-power generation fabric, including a conductive inner core and a cellulose cortex layer modified with positive and negative electrodes; wherein the conductive inner core is a silver-plated cellulose filament, and the cellulose cortex layer is divided into a modified positive electrode cellulose filament and a modified negative electrode cellulose filament.
[0010] Preferably, the modified positive electrode cellulose filaments are amino-modified cellulose filaments.
[0011] Preferably, the modified negative electrode cellulose filaments are fluorine-based modified cellulose filaments.
[0012] Preferably, the friction nano-electric power generation fabric is a skin-core structure, and the positive and negative electrode modified cellulose skin layer tightly wraps the conductive inner core; the friction nano-electric power generation fabric is prepared using a high-speed braiding machine.
[0013] Further preferably, the gear ratio of the high-speed braiding machine is 0.2-0.7.
[0014] More preferably, the gear ratio of the high-speed braiding machine is 0.3-0.5.
[0015] Then, the present invention provides a method for preparing the above-mentioned friction nano-electricity generating fabric, comprising the steps of:
[0016] (1) Preparation of silver-coated cellulose filaments (AgNPs CNFs): After pre-treatment, the cellulose filaments are reacted with a dopamine solution, and then the cellulose filaments after the reaction with the dopamine solution are taken out and placed in a silver ion solution for a silver mirror reaction to obtain silver-coated cellulose filaments;
[0017] (2) preparing modified positive electrode cellulose filaments: immersing the cellulose filaments in a positive electrode modified silane hydrolyzate, and subjecting the cellulose filaments to ultrasonic treatment and heat treatment to obtain modified positive electrode cellulose filaments;
[0018] (3) preparing modified negative electrode cellulose filaments: soaking the cellulose filaments in a negative electrode modified silane hydrolyzate, and heating and soaking to obtain modified positive electrode cellulose filaments;
[0019] (4) Preparation of friction nanogenerator yarn (CNF-FTENG): Using a high-speed braiding machine and adjusting the gear ratio, a friction nanogenerator yarn with a skin-core structure was prepared;
[0020] (5) Preparation of friction nanostructured electricity generation fabric (CNF-TTENG): A cellulose-based air layer friction nanostructured electricity generation fabric with a dual-electrode mode was woven using a knitting process.
[0021] Preferably, in step (1), the pretreatment is ultrasonic treatment in an organic solvent.
[0022] Further preferably, the organic solvent is selected from at least one of ethanol and methanol; the ultrasonic treatment time is 10-60 min, and the ultrasonic treatment power is 300-600W.
[0023] Preferably, in step (1), the concentration of the dopamine solution is 0.1-0.5 wt %, the pH is 8-9, and the reaction is carried out at room temperature for 18-48 h.
[0024] More preferably, the concentration of the dopamine solution is 0.2-0.4 wt %, the pH is 8.3-8.6, and the reaction is carried out at room temperature for 20-30 hours.
[0025] Preferably, in step (1), the silver ion solution is a silver nitrate (AgNO3) solution with a concentration of 1-3 wt%.
[0026] Preferably, in step (1), the silver mirror reaction further requires the addition of glucose solution for silver mirror reaction, the reaction time is 1-4 hours, and the reaction temperature is room temperature.
[0027] Further preferably, the concentration of the glucose solution is 1.5-4.5 wt %; and the time of the silver mirror reaction is 2 h.
[0028] Preferably, in step (2), the modification is amino modification.
[0029] Preferably, in step (2), the positive electrode modified silane hydrolyzate comprises a positive electrode modified silane coupling agent, ethanol and water; the positive electrode modified silane coupling agent, ethanol and water are mixed and stirred in a volume ratio of 0.5-2:5-10:2.
[0030] Further preferably, the volume ratio is 1-1.5:7-9:2; and the stirring time is 10-60 min.
[0031] More preferably, the positive electrode modified silane coupling agent is 3-(2-aminoethylamino)propylmethyldimethoxysilane (AEAPDMS).
[0032] Preferably, in step (2), the ultrasonic treatment is carried out for 1-15 min at a power of 300-600 W.
[0033] Preferably, in step (2), the heat treatment is carried out at a temperature of 110-130° C. for 10-18 h; more preferably, the temperature is 115-125° C. for 12-15 h.
[0034] Preferably, in step (2), after the heat treatment, the cellulose filaments are washed and dried to obtain modified positive electrode cellulose.
[0035] Preferably, in step (3), the modification is fluorine-based modification.
[0036] Preferably, in step (3), the negative electrode modified silane hydrolyzate comprises a negative electrode modified silane coupling agent, ethanol and water; the negative electrode modified silane coupling agent, ethanol and water are mixed and stirred in a volume ratio of 0.5-2:60-100:20.
[0037] Further preferably, the volume ratio is 1-1.5:70-90:20; and the stirring time is 60-180 min.
[0038] Further preferably, the negative electrode modified silane coupling agent is triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane (PFOTES).
[0039] Preferably, in step (3), the temperature of the heating soaking is 70-95° C., and the soaking time is 4-8 hours.
[0040] More preferably, the temperature of the heating soaking is 75-90° C., and the soaking time is 5-7 hours.
[0041] Most preferably, the temperature of the heated soaking is 80° C. and the soaking time is 6 hours.
[0042] Preferably, in step (4), the gear ratio is 0.2-0.7; more preferably 0.3-0.5; most preferably 0.3.
[0043] Finally, the present invention provides the application of the above-mentioned friction nano-power generation fabric in smart fire-fighting uniforms and smart power generation gloves.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The friction nano-electric power generation fabric of the present invention uses silver-plated cellulose filaments as the conductive inner core, and performs positive electrode modification and negative electrode modification operations on the cellulose filaments respectively, thereby respectively improving the electron loss capacity (positive electrode modification) and electron gain capacity (negative electrode modification) of the cellulose outer friction layer, so that the electrical output performance of the friction nano-electric power generation fabric can be significantly improved when used; the friction nano-electric power generation fabric of the present invention only uses cellulose as the material matrix, is green and environmentally friendly, and can be completely degraded within 72 hours.
[0046] 2. The conductive inner core in the friction nano-electric power generation fabric of the present invention adopts a specific dopamine solvent for reaction during its preparation, and then is mixed with a silver nitrate solution under the action of glucose. After a silver mirror reaction, silver-plated cellulose filaments with good conductivity are obtained. The filaments have good water washing resistance and still have stable electrical output performance after 20 washings.
[0047] 3. In the preparation method of the friction nano-electric power generation fabric of the present invention, the cellulose filaments are modified separately to improve the electron gain and loss ability of the cortical structure of the friction nano-electric power generation yarn; wherein, during the preparation process of the modified positive electrode cellulose filaments, when modified with the silane hydrolyzate of AEAPDMS, it needs to undergo ultrasound and heat treatment at a specific temperature, which can improve the friction performance while protecting the stability of the conductive inner core and the modified cortical structure, thereby improving the washability and power generation stability of the friction nano-electric power generation fabric.
[0048] 4. The present invention adopts a high-speed weaving process to prepare friction nano-generator yarn. The change of gear ratio affects the outer layer wrapping density, weaving angle, and composite yarn diameter. This application uses a gear ratio of 0.3-0.7, and the outer friction layer of the obtained CNF-FTENG is tightly wrapped, which is beneficial to the improvement of mechanical strength and output electrical performance. The air knitting process is used to weave the two obtained CNF-FTENGs together into a dual-electrode cellulose-based friction nano-generator fabric (CNF-TTENG) with an air change layer knitting structure, which has excellent application performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is a flow chart of the preparation of the friction nano-electricity generating fabric of the present invention;
[0050] Figure 2 is an optical microscope image of CNF-FTENG braided with different gear ratios of the present invention;
[0051] Figure 3 is the stress-strain curve of CNF-FTENG braided with different gear ratios of the present invention;
[0052] Figure 4 is the electrical output performance diagram of CNF-TTENG with different friction layers of the present invention;
[0053] Figure 5 is the electrical output performance diagram of CNF-TTENG of Example 1 of the present invention under 60N pressure at different frequencies;
[0054] Figure 6 is a graph showing the variation of the current and power density of the CNF-TTENG according to Example 1 of the present invention with the load resistance;
[0055] Figure 7 This is a stability test diagram of the CNF-TTENG of Example 1 of the present invention after being tapped 4000 times continuously;
[0056] Figure 8 is a voltage diagram for detecting the water washability of CNF-TTENG according to Example 1 of the present invention;
[0057] Fig. 9are photos and SEM images of CNF-TTENG in Example 1 of the present invention at different degradation times in a cellulase solution;
[0058] Fig.10 is a comparison chart of the degradation mass percentage of CNF-TTENG in the degradation process of Example 1 of the present invention;
[0059] Fig.11 is a detection signal diagram of finger bending by CNF-TTENG of the present invention;
[0060] Fig.12 is a detection signal diagram of elbow bending by CNF-TTENG of the present invention;
[0061] Fig.13 This is the detection signal diagram of CNF-TTENG of the present invention for walking and running;
[0062] Fig.14 is a preparation flow chart of silver-plated CNF-F of the present invention and a SEM image of silver-plated CNF-F;
[0063] Fig.15 It is a flow chart of the amino modification of CNF-F of the present invention and a SEM image of the modified positive electrode cellulose;
[0064] Fig.16 It is a flow chart of the fluorine-based modification of CNF-F of the present invention and a SEM image of the modified negative electrode cellulose. DETAILED DESCRIPTION
[0065] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0066] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs.
[0067] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Reagents from different manufacturers in the present invention have no significant effect on the effects.
[0068] In the following examples, the dopamine solution was purchased from Aladdin with the item number D103111; the AEAPDMS was purchased from Aladdin with the item number A115357; and the PFOTES was purchased from Aladdin with the item number T162293. The high-speed braiding machine model was XD05-8D-4T, purchased from Jiangsu Xiangdao Precision Machinery Co., Ltd.
[0069] Example 1
[0070] A biodegradable friction nano-electricity generating fabric, the preparation process of which is as follows Figure 1 As shown, the preparation method thereof comprises the steps of:
[0071] (1) The preparation method of silver-coated CNF-F (AgNPs CNFs) is as follows: soak CNF-F (cellulose filaments) in ethanol and ultrasonically treat for 15 minutes (400W) for pretreatment; then put the pretreated CNF-F into a dopamine solution (0.3wt%) with a pH of 8.5 and immerse it at room temperature for 24 hours; finally, put the CNF-F treated with the dopamine solution into a 1.4wt% silver nitrate (AgNO3) solution, and then add a 2.5wt% glucose solution and react at room temperature for 2 hours to complete the silver mirror reaction, so that silver nanoparticles are evenly and tightly attached to the inside and outside of CNF-F, and AgNPs CNFs with good electrical conductivity are obtained. The preparation flow chart of silver-coated CNF-F and the SEM image of silver-coated CNF-F are shown in Figure 2. Fig.14 As shown, (a) is the preparation flow chart of silver-plated CNF-F, and (b) is the SEM image of silver-plated CNF-F.
[0072] (2) The method of amino modification of CNF-F is as follows: a silane hydrolyzate (positive electrode modified silane hydrolyzate) with a volume ratio of 3-(2-aminoethylamino)propylmethyldimethoxysilane (AEAPDMS): ethanol: water of 1:8:2 is prepared for amino modification of CNF-F, and the preparation process is stirring at room temperature for 30 minutes. CNF-F is immersed in the positive electrode modified silane hydrolyzate, ultrasonically treated at room temperature for 5 minutes (400W), and then heat treated at 120℃ for 13 hours, washed and dried to obtain amino CNF filaments (AEAPDMS CNFs), which improves the electron loss capacity of the cellulose outer friction layer.
[0073] The preparation flow chart of CNF-F amino modification and the SEM image of modified positive electrode cellulose are shown in Figure 2. Fig.15 As shown, (a) is the flow chart of CNF-F amino modification, and (b) is the SEM image of modified positive electrode cellulose (AEAPDMS CNFs).
[0074] (3) The method for fluorine-modification of CNF-F is as follows: prepare a silane hydrolyzate (negative electrode modified silane hydrolyzate) with a volume ratio of triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane (PFOTES): ethanol: water of 1:80:20 for fluorine-modification of CNF-F, and stir at room temperature for 2 hours. The CNF-F is immersed in the negative electrode modified silane hydrolyzate at 80°C for 24 hours, washed and dried to obtain fluorine-modified CNF filaments (PFOTES CNFs), thereby improving the electron-accepting capacity of the cellulose outer friction layer.
[0075] Flow chart of CNF-F fluorine-based modification and SEM images of modified negative electrode cellulose are shown in Figure 2. Fig.16 As shown, (a) is the flow chart of fluorine-based modification of CNF-F, and (b) is the SEM image of modified negative electrode cellulose (PFOTES CNFs).
[0076] (4) Preparation of friction nanogenerator yarn (CNF-FTENG): The XD05-8D-4T high-speed braiding machine was used to continuously prepare flexible and degradable friction nanogenerator yarn (CNF-FTENG) with a skin-core structure. Silver-coated CNF-F (AgNPsCNFs) was wound on the center axis of the high-speed braiding machine, and AEAPDMS CNFs or PFOTES CNFs were used as outer yarns and fixed on the 8 spools of the braiding machine. After turning on the braiding machine, as the braiding machine rotates, half of the outer yarns rotate clockwise and the other half rotate counterclockwise, thereby forming a dense outer friction layer around the AgNPs CNFs, thereby obtaining amino-based CNF composite yarns (AEAPDMS / AgNPs CNFs yarns) and fluorinated CNF composite yarns (PFOTES / AgNPsCNFs yarns) with skin-core structures, respectively. These two composite yarns can be used as CNF-FTENG for the subsequent weaving preparation of CNF-TTENG.
[0077] In this step, the gear ratios of the high-speed braiding machine were adjusted to 0.3, 0.4, 0.5, 0.6, and 0.7, respectively, to obtain CNF-FTENGs prepared with different gear ratios, which were subjected to surface morphology detection using an optical microscope.
[0078] Optical microscope images of CNF-FTENG braided with different gear ratios are shown in Figure 2 , where (a) gear ratio = 0.3, (b) gear ratio = 0.4, (c) gear ratio = 0.5, (d) gear ratio = 0.6, and (e) gear ratio = 0.7.
[0079] The stress-strain curves of CNF-FTENG braided with different gear ratios are shown in Figure 3 .
[0080] The study found that when the gear ratio is 0.3, the outer friction layer of the obtained CNF-FTENG is most tightly wrapped, which is beneficial to the improvement of mechanical strength and output electrical performance.
[0081] (5) Preparation of friction nanostructured electricity generating fabric (CNF-TTENG): The two CNF-FTENGs were knitted together into a dual-electrode cellulose-based friction nanostructured electricity generating fabric (CNF-TTENG) with an air change layer knitted structure using a knitting process, and the electrical output performance, working stability, and degradability were tested and applied.
[0082] Comparative Example 1
[0083] Different from Example 1, the CNF-F in step (3) is not fluorine-modified, that is, the negative electrode cellulose is unmodified cellulose filaments (Original CNFs); after weaving with a high-speed weaving machine (gear ratio of 0.3), CNF-FTENG (AEAPDMS CNFs & Original CNFs) with modified positive electrode of the friction layer (skin layer) and unmodified cathode is obtained.
[0084] Comparative Example 2
[0085] Different from Example 1, the CNF-F in step (2) is not amino-modified, that is, the positive electrode cellulose is unmodified cellulose filaments (original CNFs), and after weaving with a high-speed weaving machine (gear ratio of 0.3), the friction layer (skin layer) positive electrode is unmodified and the cathode is modified CNF-FTENG (PFOTES CNFs & Original CNFs) is obtained.
[0086] Comparative Example 3
[0087] Different from Example 1, the dopamine solution in step (1) was replaced with a sodium hydroxide solution, the concentration of the sodium hydroxide solution was 0.3wt%, and the pH was adjusted to 8.5. The remaining parameters and steps were the same as those in Example 1, and the gear ratio was 0.3. The CNF-FTENG (friction nanogenerating yarn) and CNF-TTENG (friction nanogenerating fabric) of this comparative example were obtained.
[0088] Comparative Example 4
[0089] The difference from Example 1 is that the heat treatment temperature in step (2) is different, specifically, 80°C heat treatment for 13h followed by washing and drying. The remaining parameters and steps are the same as those in Example 1, and the gear ratio is 0.3. The CNF-FTENG (friction nanogenerator yarn) and CNF-TTENG (friction nanogenerator fabric) of this comparative example are obtained.
[0090] Comparative Example 5
[0091] The difference from Example 1 is that the ratio of the positive electrode modified silane hydrolyzate in step (2) is different, specifically:
[0092] A silane hydrolyzate (positive electrode modified silane hydrolyzate) with a volume ratio of 3-(2-aminoethylamino)propylmethyldimethoxysilane (AEAPDMS):ethanol:water of 1:2:8 was prepared for amino modification of CNF-F. The preparation process was stirring at room temperature for 30 minutes.
[0093] Test 1: Electrical output performance test
[0094] Testing method: Two CNF-TTENG samples were fixed on two fixtures of a linear motor. The electrodes of the two samples were connected to the positive and negative electrodes of a Keithley electrometer, respectively. The contact and separation of the two CNF-TTENG samples were achieved by periodic movement of the linear motor (frequency was 2 Hz, fixing force was 60 N). The open circuit voltage (V OC ), short circuit current (I SC ) and short-circuit charge (Q SC ) Implement real-time data collection.
[0095] The electrical output performance of the CNF-TTENG with different friction layers prepared in Example 1 and Comparative Examples 1-2 under a pressure of 60N at a frequency of 2Hz is shown in Figure 2. Figure 4 The electrical output performance results of the CNF-TTENG of Example 1 and Comparative Examples 1-5 under a pressure of 60N at a frequency of 2Hz are shown in Table 1 below.
[0096] The electrical output performance of CNF-TTENG in Example 1 under different frequencies and 60N pressure is shown in Figure 2. Figure 5 .
[0097] Table 1
[0098] sample <![CDATA[V OC (V)]]> <![CDATA[I SC (nA)]]> <![CDATA[Q SC (nC)]]> Example 1 5.78 42.9 1.96 Comparative Example 1 0.12 2.1 0.03 Comparative Example 2 0.62 7.1 0.26 Comparative Example 3 3.86 23.5 1.65 Comparative Example 4 5.68 39.4 1.83 Comparative Example 5 3.64 28.7 1.66
[0099] The current and power density of CNF-TTENG in Example 1 vary with load resistance. Figure 6 The highest power density of CNF-TTENG in Example 1 and Comparative Examples 1-5 is shown in Table 2 below.
[0100] Table 2
[0101]
[0102]
[0103] AEAPDMS / AgNPs CNFs yarn and PFOTES / AgNPs CNFs yarn were used to construct the upper and lower layers respectively, thereby weaving a dual-electrode CNF-TTENG with an air layer structure (such as Figure 1 As shown in Figure 2 ), the tight coating of the conductive inner core by the outer friction layer reduces the charge leakage, thus ensuring the excellent electrical output performance of the obtained CNF-TTENG (as shown in Figure 2 ). Figure 5 , 6 ): the open circuit voltage V of Example 1 OC =5.78V, short-circuit current I SC =42.9nA, charge Q SC =1.96nC, up to 0.35mW·m at a load resistance of 400MΩ -2 Compared with the TTENG constructed with unmodified CNF-F (Original CNFs) as the friction outer layer, the electrical output performance of the CNF-TTENG constructed with AEAPDMS CNFs and PFOTES CNFs as the outer friction layer is significantly improved (e.g. Figure 4 As shown). This is mainly because the surface of AEAPDMS CNFs is rich in amino groups, which makes it easier to lose electrons and provide more positive charges, while the surface of PFOTES CNFs is rich in fluorine groups, which makes it easier to obtain electrons and obtain more negative charges. Therefore, under the same pressure, CNF-TTENG using modified CNF-F to construct the outer friction layer will produce more surface charge density and show higher output electrical performance. After replacing the dopamine solution with sodium hydroxide solution in Comparative Example 3, the conductivity of the friction nano-power generation fabric is low and the electrical output performance is poor. After changing the ratio of the modified hydrolyzate in Comparative Example 5, the modification is not thorough, which affects its electrical output performance.
[0104] Test 2: Stability and water washability test
[0105] Stability performance detection method: A long-period cyclic test experiment was set up, and the CNF-TTENG was continuously tapped for 2000s under a 60N impact at a frequency of 2Hz to test the electrical output performance of the CNF-TTENG during the tapping period.
[0106] The stability test of CNF-TTENG in Example 1 after 4000 consecutive taps is shown in the figure. Figure 7 , where the left figure is a detailed voltage change diagram for the first 10 cycles, and the right figure is a detailed voltage change diagram for the last ten cycles. The stability test results of the CNF-TTENG of Example 1 and Comparative Examples 1-5 after 4000 consecutive tappings are shown in Table 3 below.
[0107] Table 3
[0108]
[0109]
[0110] Washability test method: Place a beaker containing laundry detergent and tap water on a magnetic stirrer and add a magnet to simulate a household drum washing machine. Place CNF-TTENG in the beaker. Set the rotation speed to 500 rpm, wash for about 20 minutes each time, and then place it in a 60°C oven to dry for 30 minutes. Test the electrical output performance of CNF-TTENG after each wash for 20 times.
[0111] The voltage diagram of the water washability test of CNF-TTENG in Example 1 is shown in Figure 8 The water washability test voltages of CNF-TTENG of Example 1 and Comparative Examples 1-5 are shown in Table 4 below.
[0112] Table 4
[0113] sample <![CDATA[V after 20 times of washing]]> OC (V)]]> Example 1 6.27 Comparative Example 1 0.14 Comparative Example 2 0.66 Comparative Example 3 3.33 Comparative Example 4 1.25 Comparative Example 5 3.61
[0114] The CNF-TTENG of the present invention exhibits excellent cycle stability (4000s) ( Figure 7 As shown) and water washability (as Figure 8 shown).
[0115] In Comparative Example 4, high-temperature heat treatment was not performed during amino modification, which resulted in poor durability and water-wash resistance of the material.
[0116] Test 3 Degradation performance test
[0117] Detection method: Add 0.5% 1,4-β-D-glucan glucoside hydrolase to a HAc-NaAc buffer (pH 4.8) with a volume ratio of 3:2 to prepare a cellulase degradation solution. Soak the CNF-TTENG sample in this suspension in a 50°C water bath. Observe the morphology of the sample at different stages of the degradation process and test the mass loss percentage.
[0118] The photos and SEM images of the CNF-TTENG of Example 1 of the present invention at different degradation times in the cellulase solution are shown in Fig. 9 , where, (a) 0h; (b) 12h; (c) 24h; (d) 36h; (e) 48h; (f) 60h.
[0119] The comparison of the degradation mass percentage of CNF-TTENG in the degradation process of Example 1 of the present invention is shown in Fig.10 .
[0120] Since the raw materials used to construct CNF-TTENG, including AgNPs CNFs, AEAPDMS CNFs, and PFOTES CNFs, all have good biodegradability, CNF-TTENG is endowed with good biodegradability. When CNF-TTENG is placed in a cellulase environment, it can be completely degraded within 72 hours.
[0121] Test 4 Application Example
[0122] Application method: Wear the fabric of Example 1 on the human body, and realize self-powered sensing of the human body by monitoring the changes in electrical signals transmitted by the fabric when the limbs move (including bending of fingers, bending of elbows, walking steps, etc.).
[0123] like Figure 11-13 As shown, the CNF-TTENG can be worn on the human body to monitor the movement of human limbs, thereby meeting the self-powered sensing needs of smart fire suits.
[0124] Fig.11 The detection signal diagram of CNF-TTENG for finger bending; Fig.12 This is the detection signal diagram of CNF-TTENG for elbow bending; Fig.13 This is the detection signal diagram of CNF-TTENG for walking and running.
[0125] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a biodegradable friction nano-electricity generating fabric, characterized in that: Includes steps: (1) Preparing silver-plated cellulose filaments: pre-treating the cellulose filaments and reacting them with a dopamine solution, then taking out the cellulose filaments after the reaction with the dopamine solution and placing them in a silver ion solution to perform a silver mirror reaction, thereby preparing silver-plated cellulose filaments; (2) Preparing modified positive electrode cellulose filaments: immersing cellulose filaments in a positive electrode modified silane hydrolyzate, and subjecting the cellulose filaments to ultrasonic treatment and heat treatment to obtain modified positive electrode cellulose filaments; the positive electrode modified silane hydrolyzate comprises a positive electrode modified silane coupling agent, ethanol and water; the positive electrode modified silane coupling agent, ethanol and water are mixed and stirred in a volume ratio of 0.5-2:5-10:2; the positive electrode modified silane coupling agent is 3-(2-aminoethylamino)propylmethyldimethoxysilane; the ultrasonic treatment is performed for 1-15 min at a power of 300-600 W; the heat treatment is performed at a temperature of 110-130° C. for 10-18 h; (3) Preparing modified negative electrode cellulose filaments: soaking the cellulose filaments in a negative electrode modified silane hydrolyzate, and heating and soaking to obtain modified negative electrode cellulose filaments; the negative electrode modification is fluorine-based modification; (4) Preparing friction nanogenerator yarns: using a high-speed braiding machine, adjusting the gear ratio, using the silver-plated cellulose filaments of step (1) as the core layer, and using the modified positive electrode cellulose filaments of step (2) or the modified negative electrode cellulose filaments of step (3) as the skin layer, respectively, to prepare friction nanogenerator yarns with skin-core structures; (5) Preparation of friction nano-electricity generating fabrics: The two friction nano-electricity generating yarns with a skin-core structure prepared in step (4) are woven into a cellulose-based air layer friction nano-electricity generating fabric with a dual-electrode mode by a knitting process.
2. The preparation method according to claim 1, characterized in that: In step (1), the pretreatment is ultrasonic treatment in an organic solvent, the organic solvent is selected from at least one of ethanol and methanol, the ultrasonic treatment time is 10-60 min, and the ultrasonic treatment power is 300-600 W; the concentration of the dopamine solution is 0.1-0.5wt%, the pH is 8-9, and the reaction is carried out at room temperature for 18-48h; the silver ion solution is a silver nitrate solution with a concentration of 1-3wt%; the silver mirror reaction also requires the addition of glucose solution for silver mirror reaction, the reaction time is 1-4h, and the reaction temperature is room temperature; the concentration of the glucose solution is 1.5-4.5wt%.
3. The preparation method according to claim 1, characterized in that: In step (2), the heat treatment is carried out at a temperature of 115-125°C and for a time of 12-15 hours.
4. The preparation method according to claim 1, characterized in that: In step (3), the negative electrode modified silane hydrolyzate comprises a negative electrode modified silane coupling agent, ethanol and water; the negative electrode modified silane coupling agent, ethanol and water are mixed and stirred in a volume ratio of 0.5-2:60-100:20; the negative electrode modified silane coupling agent is triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane; the heating immersion temperature is 70-95°C, and the immersion time is 4-8h; in step (4), the gear ratio is 0.2-0.
7.
5. The biodegradable friction nano-electricity generating fabric prepared by the preparation method according to any one of claims 1 to 4, characterized in that: It includes a conductive inner core and a positive and negative electrode modified cellulose cortex layer; wherein the conductive inner core is a silver-plated cellulose filament, and the cellulose cortex layer is divided into a modified positive electrode cellulose filament and a modified negative electrode cellulose filament.
6. The friction nanostructured electricity generating fabric according to claim 5, characterized in that: The modified positive electrode cellulose filaments are amino-modified cellulose filaments; the modified negative electrode cellulose filaments are fluorine-based modified cellulose filaments.
7. The friction nanostructured electricity generating fabric according to claim 5, characterized in that: The friction nano-electricity generating fabric is a skin-core structure, wherein the positive and negative electrode modified cellulose skin layers tightly wrap the conductive inner core; the friction nano-electricity generating fabric is prepared by using a high-speed braiding machine; the gear ratio of the high-speed braiding machine is 0.2-0.
7.
8. The application of friction nano-power generation fabric in smart firefighting suits and smart power generation gloves is characterized by: The friction nano power generation fabric is the friction nano power generation fabric prepared by the preparation method described in any one of claims 1 to 4, or the friction nano power generation fabric described in any one of claims 5 to 7.
Citation Information
Patent Citations
A triboelectric nanofiber fabric
CN109123854B
A co-alkali system for in-situ self-assembly of cellulose / graphene composite fibers and its preparation method
CN109913965B
Modified cellulose nanofibril-based flexible friction nano-generator
CN111082698A
Flexible self-powered sensor and preparation method thereof
CN114959998A